Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1590/s0074-02762002000800017
|View full text |Cite
|
Sign up to set email alerts
|

Mtp-40 and alpha antigen gene fragment amplification for the detection of Mycobacterium tuberculosis in Colombian clinical specimens

Abstract: In this study, the use of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…55-75%: Haas et al 2000;Zink et al 2001a;Fletcher et al 2003;Zink et al 2003). These latter data compare favourably with published rates of detection using simple PCR-based systems on modern, diagnosed, clinical samples, which are around 80% (Portillo-Gomez et al 2000;Van der Spoel van Dijk et al 2000;Mitarai et al 2001;Narayanan et al 2001;Alfonso et al 2002;Yee et al 2002;Leung et al 2003;Cheng et al 2004), and higher than detection rates for blood (40%: Taci et al 2003), urine (56%: Kafwabulula et al 2002), and host DNA in studies of animal bones from temperate archaeological sites (around 10-20%: Haynes et al 2002;Edwards et al 2004). The high frequency of amplification success from archaeological samples has been attributed to the enhanced stability of the M. tuberculosis cell wall (Donoghue et al 2004).…”
Section: Discussionsupporting
confidence: 78%
“…55-75%: Haas et al 2000;Zink et al 2001a;Fletcher et al 2003;Zink et al 2003). These latter data compare favourably with published rates of detection using simple PCR-based systems on modern, diagnosed, clinical samples, which are around 80% (Portillo-Gomez et al 2000;Van der Spoel van Dijk et al 2000;Mitarai et al 2001;Narayanan et al 2001;Alfonso et al 2002;Yee et al 2002;Leung et al 2003;Cheng et al 2004), and higher than detection rates for blood (40%: Taci et al 2003), urine (56%: Kafwabulula et al 2002), and host DNA in studies of animal bones from temperate archaeological sites (around 10-20%: Haynes et al 2002;Edwards et al 2004). The high frequency of amplification success from archaeological samples has been attributed to the enhanced stability of the M. tuberculosis cell wall (Donoghue et al 2004).…”
Section: Discussionsupporting
confidence: 78%
“…Although the study of Sastry and Sandhya Bhat (2013) in India which was carried out on CSF specimens using IS6110 -nested PCR, 40.3% positive rate was achieved which was higher than our findings, probably due to their larger sample size, as the number of CSF specimens in this study was too few to make any conclusion. Also Alfonso et al (2002), in Colombia, reported a positivity rate of 74% by applying nested PCR targeting mtp40 on clinical specimens (urine, sputum, CSF, etc. ), while in present study 22% of the specimens were positive using mtp40 genes.…”
Section: Discussionmentioning
confidence: 99%